2013
DOI: 10.1016/j.jjcc.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dipstick proteinuria as a surrogate marker of long-term mortality after acute myocardial infarction

Abstract: Dipstick proteinuria and lower eGFR in the early phase of AMI follow-up were related to increased plasma BNP level during the sub-acute phase and long-term adverse outcome. Dipstick proteinuria may be a prognostic marker for long-term all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In some studies, the sensitivity and specificity of the dipstick urinalysis protein ≥ 1+ in detecting the albumin to creatinine ratio ≥ 300 has improved to ≥ 90% [35, 36]. Moreover, proteinuria measured using the dipstick technique itself is a well-validated risk factor for ESRD [2, 3] and mortality [4–6], and is still being used as the main factor or outcome [3740]. Therefore, this limitation might be marginal.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the sensitivity and specificity of the dipstick urinalysis protein ≥ 1+ in detecting the albumin to creatinine ratio ≥ 300 has improved to ≥ 90% [35, 36]. Moreover, proteinuria measured using the dipstick technique itself is a well-validated risk factor for ESRD [2, 3] and mortality [4–6], and is still being used as the main factor or outcome [3740]. Therefore, this limitation might be marginal.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there was a proliferation of new scores and methods to predict CIN [13][14][15][16][17][18]; however, their usefulness and extension to clinical practice is limited. The Mehran CIN score was designed in 2004 and based on its simplicity and because it allows early and correct identification of those individuals at high risk for CIN [5], it is currently the most widely used tool for predicting the risk of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…elderly patients, diabetes, renal dysfunction, contrast media volume, heart failure, etc.) [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Konta et al showed that proteinuria/albuminuria were independently associated with mortality in the Japanese general population [35]. Ota et al and Tonelli et al also investigated all-cause mortality in acute myocardial infarction (AMI) patients [36,37]. Both studies showed that dipstick proteinuria was an independent predictor of all-cause mortality with or without impaired kidney function.…”
Section: Discussionmentioning
confidence: 99%